(untitled) (Journal of Cancer Research Updates, 2015)
In clinical, Psychotria serpens L. was often substitute for Caulis trachelospermi to treat cancer in China. Meanwhile, EtOAc and n-BuOH fractions of MeOH extract of P. serpens L. show power activity against H460, HepG2, Hela, and PC9/GR cell lines, and no toxic effects against normal 16HBE cell lines. In order to search significant anti-cancer active leading compounds, sevenetin (5), rutin (6), kaempferol-3- flavonoids, quercetin (1), tamarixetin-3-O-rutinoside (2), quercetin 3-O-(2G-β-D-xylopyranosy-lrutinoside) (3), kaempferol (4), tamarixO- rutino- side (7) were isolated from P. serpens L., and their structures were identified through spectroscopic techniques including NMR (1D and 2D) and MS. 2-5 were the first isolated from genus Psychotria. All of compounds were the first isolated from P. serpens.